Financial Accounting Software Application for MSME Members of Baitul Maal Wat Tamwil (BMT) in South Sumatra - Soediro, Achmad; Kusumawardani, Media; Farhan, Muhammad; Adhitama, Fardinant; Yusrianti, Hasni (Faculty of Economics, Universitas Sriwijaya, 2024)
Implementation of Community Service Activities with the theme